2012
DOI: 10.1039/c2cp40922d
|View full text |Cite
|
Sign up to set email alerts
|

Dispersions of image potential states on surfaces of clean graphite and lead phthalocyanine film

Abstract: Dispersions of image potential states on a graphite surface (denoted IPS1) and on 1 monolayer (ML) film (denoted IPS2) of lead phthalocyanine (PbPc) are investigated by the micro-spot angle-resolved two-photon photoemission (micro-AR-2PPE) spectroscopy. On the graphite surface, whole dispersions of the two members of IPS1 (n = 1 and 2) are observed. The n = 1 IPS1 peak is weakly visible at energy higher than the vacuum level. The effective mass of an electron in the n = 1 IPS1 becomes slightly light at the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
7
18
0
Order By: Relevance
“…3d) yields an effective mass of 1.6 m e (m e is the free electron mass). This is consistent to previous studies [22,24] in which effective masses are found in the range of 1.0 -2.2 m e . The spectra at later times are shown in Fig.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…3d) yields an effective mass of 1.6 m e (m e is the free electron mass). This is consistent to previous studies [22,24] in which effective masses are found in the range of 1.0 -2.2 m e . The spectra at later times are shown in Fig.…”
supporting
confidence: 93%
“…Similar temporal change in the band structure is found for the 1 ML sample. Previous studies have shown that periodic potential introduced by the molecular layer can cause gap opening and band splitting at the BZ boundary [22,24]. We cannot resolve this splitting potentially because of the larger bandwidth of our laser pulses.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The data points for graphite were taken from [31], which observed the lowest three image-potential states. Other groups reported binding energies of 0.85 ± 0.10 eV for the n = 1 image-potential state [44,45]. The experimental values are slightly above the calculated lines, but the slope is in fairly good agreement.…”
Section: Binding Energiesmentioning
confidence: 58%
“…1(c). This extra peak cannot be assigned to the n=2 IPS, which is known to be 0.75 eV above the n=1 IPS and have much lower intensity [54]. In mPP spectra of the clean Gr, the Γ point of ILB does not appear because there is no initial state from where it can be excited [35].…”
mentioning
confidence: 94%